Antibacterial Activity of Bisanthraquinone (+)-1,1’-Bislunatin - PRAPTIWI PRAPTIWI; YULIASRI JAMAL; AHMAD FATHONI; ARIF NURKANTO; ANDRIA AGUSTA (Microbiology Indonesia, 2013)
Endophytic fungi has been known as a source of biologically active compunds with a broad sprectrum of activities. One of the endophytic fungi isolated from young stem of gambier plant (Uncaria gambier Roxb.:Rubiaceae), Diaporthe sp. GNBP-10, produced (+)-1,1’-bislunatin when cultivated on potato dextrose agar (PDA). (+)-1,1’-Bislunatin showed moderate antibacterial activity against 7 bacteria (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Micrococcus luteus, Shigella flexneri, Proteus vulgaris, and P. mirabilis) with MIC value in the range of 32-64 µg mL-1. The wall disruption and morphological changes in the cells affected by exposure of (+)-1,1’-bislunatin are also discussed in this article.